Prevalence and risk factors of anxiety and depression in Chinese patients with lung cancer: a cross-sectional study - Yan X; Chen X; Li M; Zhang P (Cancer Management and Research, 2019)
Xiaoru Yan,1,2,* Xun Chen,3,4,* Meng Li,1,3 Peitong Zhang11Department of Oncology, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China; 2Graduate School, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 3Graduate School, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 4Department of Gastroenterology, Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China *These authors contributed equally to this workBackground: Lung cancer is very common in China. The low cure rate, limited overall survival, and continuous therapies lead the patients to experience considerable psychological distress. Traditional Chinese medicine therapy is one unique treatment method in China. Nevertheless, most patients in the existing studies on anxiety and depression were treated in western medical hospitals. Therefore, it is necessary to identify the prevalence and risk factors of these emotional disorders in lung cancer patients treated in traditional Chinese medical hospitals. These findings may assist in clinical intervention.Patients and methods: A total of 315 patients with lung cancer were enrolled. Individuals completed the Hospital Anxiety and Depression Scale to assess their levels of anxiety and depression. Demographic and clinical data were also collected. Binary logistic regression analysis was used to identify factors that significantly predicted anxiety and depression.Results: The anxiety and depression prevalence rates of lung cancer patients were 43.5% and 57.1%, respectively. In the univariate analysis, patients without surgery, who were young, or who received radiotherapy were more likely to experience anxiety. Patients without surgery, who were young, or who had late-stage cancer, were more likely to experience depression. Binary logistic regression analysis showed that the risk factors of both anxiety and depression were lack of surgery and young and middle age (＜65, especially 45–65 years).Conclusion: Anxiety and depression were very common in lung cancer patients. Lack of surgery, young, and middle age, were independent risk factors for anxiety and depression. Therefore, medical workers should pay close attention to the emotional changes of young or middle-aged patients, or patients without the chance to undergo surgery.Keywords: anxiety, depression, lung cancer, mental health